PENGARUH SELF EFFICACY, TEAM WORK DAN WORK LIFE BALANCE TERHADAP KINERJA KARYAWAN PT FINANSIA MULTI FINANCE (KREDIT PLUS) KOTA BENGKULU - Ferdiansyah, Dimas; Armi, Muhammad Noor; ., Fauzan (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2023)
This study aims to determine the effect of self efficacy, team work and work life balance on employee performance at PT Finance Multi Finance (Credit Plus) Bengkulu City. Self efficacy,teamwork and work life balance are the variables of this study. Data collection techniques by distributing questionnaires using a scale likert instrument. The entire PT Employee Multi Finance Finance (Kredit Plus) Bengkulu City is the study population. Using the saturated sample method 38 samples This research uses the SPSS 22 analysis program. Multiple linear regression analysis Classical hypothesis test t test F test multiple correlation, the coefficient of determination is also used techniques used for data analysis. The results only show that (1) self efficacy affects the performance employees of PT Finansia Multi Finance. (2) Team work at PT Finansia Multi Finance (Kredit Plus) does not affect employee performance (3) Employee Performance PT Finansia Multi Finance (Kredit Plus) Bengkulu City is influenced by work life balance. (4) self efficacy, team work and work life balance have a simultaneous effect on the performance of Finansia Multi Finance (Kredit Plus) Bengkulu City employees.